## College Algebra (10th Edition)

Published by Pearson

# Chapter 1 - Section 1.3 - Complex Numbers; Quadratic Equations in the Complex Number System - 1.3 Assess Your Understanding - Page 112: 70

#### Answer

$\displaystyle \{-3,\frac{3}{2}-\sqrt{6}i,\frac{3}{2}+\sqrt{6}i\}$

#### Work Step by Step

Recognize a sum of cubes, $x^{3}+3^{3}=(x+3)(x^{2}-3x+3^{2})$ One solution is $x=-3$ For the other two, solve $x^{2}-3x+9=0$ Use the quadratic formula $a=1, b=-3, c=9$ $x=\displaystyle \frac{-b\pm\sqrt{b^{2}-4ac}}{2a}$ $x=\displaystyle \frac{3\pm\sqrt{9-36}}{2}=\frac{3\pm\sqrt{-24}}{2}$ ...If $N$ is a positive real number, we define the principal square root of $-N,$ denoted by $\sqrt{-N},$ as $\sqrt{-N}=\sqrt{N}i$ $=\displaystyle \frac{3\pm i\sqrt{24}}{2}$ $=\displaystyle \frac{3}{2}\pm\frac{2\sqrt{6}}{2}i$ $=\displaystyle \frac{3}{2}\pm\sqrt{6}i$ Solution set = $\displaystyle \{-3,\frac{3}{2}-\sqrt{6}i,\frac{3}{2}+\sqrt{6}i\}$

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.